Ocelliemesina sinica, the second ocelli-bearing genus and species of thread-legged bugs (Hemiptera: Reduviidae: Emesinae) - Wang, Jianyun; Wang, Baohai; Cao, Liangming; Cai, Wanzhi (Zootaxa, 2015)
Ocelliemesina sinica, gen. & sp. nov., from Yunnan Province, China is described. It represents the second genus and species with ocelli in the reduviid subfamily Emesinae. Dorsal habitus, male genitalia, and other diagnostic morphological characters of the new species are illustrated. The type specimen is preserved in the Entomological Museum of China Agricultural University, Beijing.